Upaya Penyuluh Agama Islam Dalam Mengurangi Pernikahan Usia Dini di Binjai Selatan - Fadhil, Muhammad; Abdurrahman, Zulkarnain (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
In Indonesia there are many cases of early marriage. Even though early marriage is permissible according to Islamic law, if it is not carried out according to the provisions it will cause a lot of harm. The purpose of this qualitative research is to be able to find out what efforts were made by Islamic Religious Extensionists in reducing early marriage in South Binjai City through observation and in-depth interviews. The informant was an Islamic Counselors in South Binjai. The results of the study show that the efforts of Islamic Counselors at South Binjai to reduce early marriage are carried out in various ways, including by socializing the Marriage Law No. 1 of 1974 and providing religious guidance to parents and adolescents every month in different locations regarding the purpose of marriage and the negative impacts of early marriage. Apart from that, they also cooperates with village heads and neighborhood heads in providing education for residents who want to marry early. This effort is very helpful in reducing the number of early marriages in South Binjai in 2022.